Long-Term Outcome of Thrombolytic Therapy for Massive Pulmonary Embolism in Pregnancy - Sy Van Hoang; Anh Tuan Vo; Kha Minh Nguyen (Case Reports in Cardiology)
A 25-year-old pregnant woman presented at 12 weeks of gestation with syncope and shortness of breath caused by massive pulmonary embolism. Due to persistent shock, fibrinolytic therapy with rtPA was administered. After fibrinolysis, clinical and hemodynamic response was excellent. No bleeding and fetal complications were recorded.